Narrowband Registration of Ultra-Wideband Signal. (January 2016) - Kamenev, A V; Satarov, R N; Yakubov, V P; Shipilov, S E
Abstract: The research of various parameters influence on the Fresnel reflector focusing properties in particular spatial sizes, the focal point position, etc. is conducted. The version of using a flat Fresnel reflector for receiving ultra-wideband signals with the use of Wiener filtering is suggested.